Piano sonata in C-sharp minor, op. 27, no. 2, published by Simrock - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Guicciardi, Giulietta, 1784-1856 (dedicatee):::Contributor:::::::::::: (Germany; N. Simrock; Bonn)
Piano sonata no. 14 in C# Minor, op. 27, no. 2, in later issue of the Simrock edition first published in 1802